The tensions of uncertainty: Midwives managing risk in and of their practice. (July 2016) - Skinner, Joan; Maude, Robyn
Abstract: The tensions of uncertainty: midwives managing risk in and of their practice. There has been a fundamental shift in past decades in the way midwifery is enacted. The midwifery attributes of skilful practice and conscious alertness seem to have been replaced by the concept of risk with its connotations of control, surveillance and blame. How midwifery manages practice in this risk framework is of concern. Taking a critical realist approach this paper reports on a theoretically and empirically derived model of midwifery undertaken with New Zealand midwives. The model is a three legged birth stool for the midwife which describes how she makes sense of risk in practice. The seat of the stool is being with women and the legs are 'being a professional', 'working the system' and 'working with complexity'. The struts which hold the stool together are 'story telling'. Risk theory is reviewed in light of the empirical study and a theoretical gap of uncertainty and complexity are identified. Highlights: The research takes a critical realist approach using mixed methods. It examines referral for obstetric consultation of New Zealand midwives. The model identifies complexity and uncertainty as important issues for midwives which remain undertheorised.